2007
DOI: 10.1161/01.str.0000254596.81137.51
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Stenosis Index Revisited With Direct CT Angiography Measurement of Carotid Arteries to Quantify Carotid Stenosis

Abstract: Background and Purpose— All carotid stenosis ratio methods are based on the inability of digital subtraction angiography to measure in millimeters. Each method has potential flaws. The Carotid Stenosis Index (CSI) was designed to reduce ambiguities of NASCET and ECST ratios. We test this method’s ability to correctly estimate carotid stenosis using direct computed tomography angiography millimeter measures of the carotid arteries. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…Plaque characteristics such as lipid-rich core, fibrous cap thickness, and intraplaque hemorrhage have been demonstrated on sonography [4][5][6] and MR imaging, [7][8][9][10][11][12][13][14][23][24][25] and it is suggested that these ancillary features, taken in conjunction with the degree of stenosis, may be important predictors of future stroke risk. CT angiography is being increasingly used to noninvasively image carotid stenosis 26,27 and has also been shown to be useful in the evaluation of carotid plaque morphology. 15,17,[28][29][30][31] The findings from our study indicate that apart from increasing degree of stenosis, the presence of an intraluminal thrombus is highly predictive of the symptomatic side in patients with carotid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque characteristics such as lipid-rich core, fibrous cap thickness, and intraplaque hemorrhage have been demonstrated on sonography [4][5][6] and MR imaging, [7][8][9][10][11][12][13][14][23][24][25] and it is suggested that these ancillary features, taken in conjunction with the degree of stenosis, may be important predictors of future stroke risk. CT angiography is being increasingly used to noninvasively image carotid stenosis 26,27 and has also been shown to be useful in the evaluation of carotid plaque morphology. 15,17,[28][29][30][31] The findings from our study indicate that apart from increasing degree of stenosis, the presence of an intraluminal thrombus is highly predictive of the symptomatic side in patients with carotid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplanar reformation of MRA data can solve this problem by aligning the image plane perpendicular to the ICA to optimize measurement of eccentric stenosis. 30 The disadvantages of MPR evaluation are the inferior 3D visualization of the vessels and higher time demand to adjust the image planes. Volume-rendering techniques optimally visualize vessels in 3 dimensions, but the parameter setting of the transfer function is critical for morphologic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…4 Bartlett et al have now harnessed the inevitable advances in imaging technology and have used computed tomography angiography (CTA) to directly measure carotid stenosis using screen calipers applied to contrast luminograms of the carotid bulb. 9 Their message seems to be that measurements of carotid stenosis should be direct and individualized, not generalized, by CTA measurement of the diameters of the carotid bulb and the atheromatous stenosis. However, CTA is not without technological difficulties.…”
Section: To the Editormentioning
confidence: 99%
“…As the authors note, using CTA indeed involves a new measurement paradigm for carotid stenosis. 9 The authors attempt at comparison with the CSI method falls short because of the methodology used. 9 Critically, the CTA measurements (carotid bulb stenosis and carotid bulb diameter) are made on contrast luminogram axial images at the level of tightest stenosis, ie, both the stenosis and the carotid bulb diameter are measured at the same location.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation